Effects of the Corporate Governance Practices on the Executive Compensation - Giselle Cilaine Ilchechen Coelho; Joaquim Rubens Fontes Filho; Felipe Buchbinder (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
This study aims to identify the effect of the quality of corporate governance practices on the configurations and values of executive compensation. According to agency theory, good corporate governance practices contribute to reducing information asymmetries between shareholders and managers and, consequently, the potential for managerial opportunism, reducing the need for incentives to align interests. In this sense, three hypotheses were elaborated relating the quality of corporate governance practices of companies with (1) the executive remuneration values, (2) the conformity gap, and (3) the share held by the CEO in relation to the other members of the C -level (CEO pay slice). These hypotheses were verified for companies listed in the Brazilian stock market, characterized by the predominance of concentrated ownership. Based on a sample of 174 companies with the highest liquidity, accounting for about 40% of the universe, and using as control variables the size of the company and its sector of activity, no significant effects of the quality of governance were observed on the remuneration structures executive share or on the CEO's share of the C-level total. However, a significant relationship between the quality of governance and compliance with good remuneration practices was observed, evidencing a lower conformity gap. The results contribute to the governance and executive remuneration literature by pointing out potencial flaws in agency theory and information asymmetries as justification for executive compensation practices.
Keywords: 650; agency theory; CEO pay slice; conformity gap; corporate governance; executive compensation